Role of Mas Receptor Antagonist A799 in Renal Blood Flow Response to Ang 1-7 after Bradykinin Administration in Ovariectomized Estradiol-Treated Rats - Aghdas Dehghani; Shadan Saberi; Mehdi Nematbakhsh (Advances in Pharmacological Sciences)
Background. The accompanied role of Mas receptor (MasR), bradykinin (BK), and female sex hormone on renal blood flow (RBF) response to angiotensin 1-7 is not well defined. We investigated the role of MasR antagonist (A779) and BK on RBF response to Ang 1-7 infusion in ovariectomized estradiol-treated rats. Methods. Ovariectomized Wistar rats received estradiol (OVE) or vehicle (OV) for two weeks. Catheterized animals were subjected to BK and A799 infusion and mean arterial pressure (MAP), RBF, and renal vascular resistance (RVR) responses to Ang 1-7 (0, 100, and 300 ng kg−1 min−1) were determined. Results. Percentage change of RBF (%RBF) in response to Ang1-7 infusion increased in a dose-dependent manner. In the presence of BK, when MasR was not blocked, %RBF response to Ang 1-7 in OVE group was greater than OV group significantly (P<0.05). Infusion of 300 ng kg−1 min−1 Ang 1-7 increased RBF by 6.9±1.9% in OVE group versus 0.9±1.8% in OV group. However when MasR was blocked, %RBF response to Ang 1-7 in OV group was greater than OVE group insignificantly. Conclusion. Coadministration of BK and A779 compared to BK alone increased RBF response to Ang 1-7 in vehicle treated rats. Such observation was not seen in estradiol treated rats.